2006
DOI: 10.1001/archinte.166.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokines and Incident Diabetes Mellitus in Older Adults

Abstract: Background: Adipose tissue produces "adipocytokines" of uncertain clinical significance. Methods: We analyzed the relationships among adiposity, adipocytokines, glycemia, and incident diabetes mellitus in 2356 white and black adults aged 70 to 79 years in the Health, Aging, and Body Composition Study who did not have diabetes at baseline. We measured the levels of adipocytokines adiponectin, leptin, interleukin 6, tumor necrosis factor ␣, and plasminogen activator inhibitor 1. Regional fat area was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 58 publications
3
36
1
Order By: Relevance
“…Levels of IL-1h, TNF-a, and PAI-1 were somewhat lower in our study than levels reported elsewhere (7,42), and the median leptin level (2.8 ng/mL) was also lower than the levels reported in the Health ABC cohort (5.5 ng/mL), the San Antonio Center for Biomarkers of Risk of Prostate cohort (7.6 ng/mL; refs. 7, 43), and in some clinical studies (24,37,43,44).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Levels of IL-1h, TNF-a, and PAI-1 were somewhat lower in our study than levels reported elsewhere (7,42), and the median leptin level (2.8 ng/mL) was also lower than the levels reported in the Health ABC cohort (5.5 ng/mL), the San Antonio Center for Biomarkers of Risk of Prostate cohort (7.6 ng/mL; refs. 7, 43), and in some clinical studies (24,37,43,44).…”
Section: Discussioncontrasting
confidence: 80%
“…Adipokines constitute a growing list of soluble polypeptides that are involved in complex signaling between white adipose tissue and systemic inflammatory, metabolic, and immunoregulatory pathways (2). Several subgroups of adipokines are currently recognized: (a) classic cytokines and chemokines such as tumor necrosis factor-a (TNF-a), interleukin-1h (IL-1h), IL-6, IL-8, IL-10, and tumor growth factor-h (TGF-h); (b) acute-phase proteins such as haptoglobin, serum amyloid-A, C-reactive protein, and plasminogen activator inhibitor-1 (PAI-1); and (c) other adipocyte-or macrophage-derived proteins, including leptin, nerve growth factor (NGF), monocyte chemoattractant protein-1 (MCP-1), resistin, and adiponectin (1,(3)(4)(5)(6)(7). An increasing number of other candidate adipokines are also being reported, including hepatocyte growth factor (HGF), the angiogenic protein vascular endothelial growth factor (VEGF), migrationinhibitory factor (MIF), and the iron-regulatory peptide hepcidin (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…In the same study high PAI-1 level was linked to diabetes incidence. [18], In Health, Aging and Body Composition Study [19] similar results were found.…”
Section: Resultssupporting
confidence: 65%
“…High levels of leptin have been shown to be independently associated with diabetes in some [8][9][10][11] but not all studies [7,[12][13][14][15]18]. Of these studies, only two were UK population based studies [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence regarding the association between leptin and type 2 diabetes risk is conflicting, with some studies showing positive associations [6][7][8][9][10][11] and others showing no association [12][13][14][15]. Similarly, the association between adiponectin and type 2 diabetes risk…”
Section: Introductionmentioning
confidence: 99%